Application of Data Mining in direct marketing - Pavlović, Dejana; Reljić, Marija M; Jaćimović, Sonja (Industrija, 2014)
The key to successful business operations lies in good communication with clients. There are a growing number of brokers in the financial market who collect excess funds from the clients and perform transfers to those who need the funds. However, many external and internal factors influence the decision on disposal of available funds. This paper identifies and researches into clients’ satisfaction in the banking system. By application of the disclosure of data legality we will try to point to the factors that influence the clients’ decision to invest their long-term deposits in the parent bank. Upon classification and clustering, we will interpret and indentify the strengths and weaknesses of the target results. This analysis provides the guidelines through the use of the decision-making tree, application of data mining and the possibility to use a large set of data increases the value and accuracy of this technique. The problem with this technique is accuracy of the data submitted by the client.